KONSEP ISHLAH DALAM HUKUM ISLAM (Perspektif tafsir Maudhu’iy) - Saidah Saidah (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2012)
Alquran is guidance of Muslim of all their actions. So, we never forget alquran as guidance to solve our (muslim’s) problems. Beside that the islamic law is based of alquran. That’s meaning all of the rules in islamic law must be based on alquran. In realities, the society of muslim appear many problems (complict) and Ishlah (peace in English term) is one of way to end the complict. According in this written, islah is the best way than the other ways to make peace who the people’ complict.